The influence of customer perceived value and perceived service performance on customer satisfaction to Malay upscale restaurants in Kuala Lumpur / Mohd Nazri Abdul Raji - Abdul Raji, Mohd Nazri (2013)
To date, popularity of Malay upscale restaurant is still outshined by other international full service restaurant that comes from different part of the world such as American, Mexican, Siamese, Spanish, French, Korean, Japanese and others. Basically the highly demand towards international full service restaurant has made local restaurants particularly Malay full service restaurants trying to be a player and taking a share of this market. This study focuses on the analyzing the influence of customer perceived value and perceived service performance on customer satisfaction to Malay upscale restaurants in Kuala Lumpur. It looks at the dimension in perceived value on emotional responses, monetary price, behavioral price and reputation. Meanwhile, the dimension in perceived service performance looks on physical environment quality, interactional quality and outcome quality. A total of 5 Malay upscale restaurants were chosen and 170 customers participated in this study. Data were collected through self-administered questionnaires. Descriptive statistics, reliability analysis, Pearson correlation and multiple analyses were used in the data analysis. Findings showed that perceived service performance has a high contribution (β=0.726, p<0.01) and determined as the most significant influence on customer satisfaction. The beta value for perceived value (β=0.646, p<0.01) was also high which indicated that it made some contribution on customer satisfaction.